New hybrid organic-zincophosphate frameworks: single-crystal-to-single-crystal structural transformation and remarkable thermal and chemical stabilities. Issue 17 (12th April 2016) - Chang, Tsung-Yuan; Yan, Zhao-Nan; Wang, Chun-Chi; Li, Hsing-Chun; Lin, Hsiu-Mei; Wang, Chih-Min
Abstract : This research is the first example of hybrid metal phosphates that undergo SCSC structural transformations and exhibit remarkable thermal and chemical stabilities. Abstract : This research is the first example of a hybrid metal phosphate that undergoes an SCSC structural transformation and provides a new route for the synthesis of organic–inorganic hybrid materials with high stabilities via the introduction of nitrogen-donor ligands into a metal–phosphate system. The synthesis, structural diversity, and thermal and chemical stabilities are also discussed.